1998
DOI: 10.1055/s-0037-1615367
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Translocation of MMP-2 during Aggregation of Human Platelets

Abstract: SummaryWe have previously shown that human platelets express matrix metalloproteinase-2 (MMP-2) and that the release of this enzyme during platelet activation mediates the ADP- and thromboxane-independent part of aggregation. We have now used immunogold electron microscopy, flow cytometry, Western blot analysis and zymography methods to study the ultrastructural localization of MMP-2 in human washed platelets. Platelet aggregation was stimulated by collagen and the MMP-2 immunoreactivity of platelets was follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 19 publications
5
115
1
4
Order By: Relevance
“…MMP-1 17 and MMP-2 18-20 were shown to prime platelets for adhesion and aggregation, whereas MMP-9 inhibited platelet activation. 19,20 However, a possible role of MMPs in PSL or the related cleavage of GPIb␣ has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMP-1 17 and MMP-2 18-20 were shown to prime platelets for adhesion and aggregation, whereas MMP-9 inhibited platelet activation. 19,20 However, a possible role of MMPs in PSL or the related cleavage of GPIb␣ has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-1 17 and MMP-2 18-20 were shown to prime platelets for adhesion and aggregation, whereas MMP-9 inhibited platelet activation. 19,20 However, a possible role of MMPs in PSL or the related cleavage of GPIb␣ has not yet been investigated.In this study, we show that specific mitochondrial damage induces morphologic and functional changes in platelets that resemble those of PSL. We further demonstrate that inhibition of platelet-derived metalloproteinase(s) during platelet in vitro aging or mitochondrial damage markedly improves the recovery of these …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets contain and release MMP-2, a gelatinase, which acts as a stimulator 31 of aggregation. Therefore, we studied the gelatinolytic activity of MMP-2 released from QD-activated platelets by gelatin gel zymography ( Figure 3A) and quantified the resultant bands ( Figure 3B).…”
Section: Qds Induce Mmp-2 Release From Plateletsmentioning
confidence: 99%
“…48 Most of these studies were performed using LTA. We have shown that LTA may not be sensitive enough for studying platelet-NP interactions, and a more [29][30][31][32][33] may be preferred. In keeping with this notion, we detected QD-induced platelet aggregation in PRP using QCM-D but not LTA.…”
mentioning
confidence: 99%